2005
DOI: 10.1177/112067210501500308
|View full text |Cite
|
Sign up to set email alerts
|

Custom Measurement of Retinal Nerve Fiber Layer Thickness Using STRATUS OCT in Normal Eyes

Abstract: These results suggest that both scan options give good RNFL thickness measurement reproducibility; the use of the Nerve Head Circle option leads to less interindividual variability and can minimize the effect of differences in optic disc diameter on RNFL thickness measurements in normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 18 publications
(31 reference statements)
3
43
1
Order By: Relevance
“…Similar results have been already reported, even if in a much smaller sample of eyes [14,21]. Other technology-based studies were conducted [6,28] with Stratus OCT in healthy eyes using RNFL thickness 3.4 and optic disc protocols and it was found that, differently from our findings, thickness increases significantly for increasing OD area [28] and diameter [6]. This discrepancy of results may be interpreted on the basis of differences in ).…”
Section: Discussioncontrasting
confidence: 48%
“…Similar results have been already reported, even if in a much smaller sample of eyes [14,21]. Other technology-based studies were conducted [6,28] with Stratus OCT in healthy eyes using RNFL thickness 3.4 and optic disc protocols and it was found that, differently from our findings, thickness increases significantly for increasing OD area [28] and diameter [6]. This discrepancy of results may be interpreted on the basis of differences in ).…”
Section: Discussioncontrasting
confidence: 48%
“…Another way to adjust for this would be to measure RNFL at a fixed relative distance from the optic disc margin. Carpineto et al 23 performed Stratus OCT measurements using the fixed 3.46-mm-diameter circle and a variable scan circle diameter designed to measure the RNFL 0.85 mm from the edge of the optic disc in the same group of 30 normal eyes. They confirmed the findings of the current studynamely, that eyes with larger optic nerves had thicker RNFL measurements-but also showed that RNFL thickness is unrelated to vertical optic disc diameter if one measures RNFL thickness a fixed distance from the disc margin.…”
Section: Discussionmentioning
confidence: 99%
“…RNFL thickness reproducibility using OCT has been studied in recent years, and authors have reported good reproducibility (Budenz et al 2005;Carpineto et al 2005). Some authors have studied RNFL measurements reproducibility obtained using the fast RNFL thickness protocol of the Stra- tus 3000 OCT system in healthy (Carpineto et al 2005) and glaucomatous eyes (Blumenthal et al 2000;Budenz et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have studied RNFL measurements reproducibility obtained using the fast RNFL thickness protocol of the Stra- tus 3000 OCT system in healthy (Carpineto et al 2005) and glaucomatous eyes (Blumenthal et al 2000;Budenz et al 2005). Some of these studies reported that nasal RNFL was the less variable sector (Budenz et al 2005).…”
Section: Discussionmentioning
confidence: 99%